Platelet GPIb complex as a target for anti-thrombotic drug development - Clemetson, Kenneth J.; Clemetson, Jeannine M. (Thrombosis and Haemostasis, 2008)
Specific inhibition of platelet function is a major target of antithrombotic drug research. Platelet receptors are both accessible and specific but have multiple functions often linked to a wide range of ligands. GPIb complex is best known as a major platelet receptor for vonWillebrand factor essential for platelet adhesion under high shear conditions found in arteries and in thrombosis. Recent animal studies have supported inhibition of GPIb as a good candidate for anti-thrombotic drug development with several classes of proteins showing important specific effects and the required discrimination between roles in haemo- stasis and thrombosis is important to protect against bleeding complications.These include antibodies, several classes of snake venom proteins, mutant thrombin molecules and peptides affecting subunit interactions.However,due to the nature of its receptor- ligand interactions involving large protein-protein interfaces, the possibility of developing classic pharmaceutical inhibitors for long term (and perhaps oral) treatment is still unclear, and additional information about structural interactions and signalling mechanisms is essential.
Keywords: Antiplatelet agents; atherothrombosis; GP Ib; platelet glycoproteins; platelet pharmacology